Regaining life after PTSD in the novel snow hunters (2013) by Paul Yoon - Antoni Suhermanto; An Fauzia Rozani Syafei (English Language and Literature, 2019)
This thesis is an analysis of the novel Snow Hunters (2013) by Paul Yoon. This analysis aims to show the extent to which the contribution of fictional elements (character, settings, and plot / conflict) gives an idea of how the main character suffering from PTSD can get his life back. This can be seen from how the main character adapts and works hard in a new place for the sake of changing his life for the better. This analysis is also based on the concept of Sublimation from Sigmund Freud. The results of this analysis show that the main character with his efforts was able to regain his life after suffering from PTSD.